An objective evaluation of the contraction power of a neophallus reconstructed with free reinnervated LD in female-to-male transsexuals - Ranno, Raul; Hýža, Petr; Veselý, Jiří; Dessy, L. A; Kadaňka, Zdeněk (Scripta medica Facultatis medicae Universitatis Brunensis Masarykianae, 2008)
Objective evaluation of the contraction power of a neophallus reconstructed with a novel technique in female-to-male transsexuals. From December 2001 to September 2005, 22 patients with gender identity disorder underwent neophalloplasty with a reinnervated latissimus dorsi free flap. All the patients were subjected to an early rehabilitation protocol of the transferred muscle; the beginning time of neophallus voluntary contraction was recorded in 18 patients. Fourteen patients who came for examinations were objectively evaluated for the strength of transplanted muscle contraction in the neophallus by electromyography and measurement of the maximum weight lifted. Eighteen patients were able to voluntarily contract the neophallus after an average period of 4.11 months. In 14 of them, the average weight lifted was 1129 grammes. After electromyography, the mean number of positive peaks in the 100 ms period was 31.5; the mean amplitude from 10 highest positive peaks, measured peak-to-peak, was 0.99 mV. The advantage of this technique is non-requirement of the prosthesis for sexual activity due to the development of strong voluntary contraction of the neophallus. Our findings document objectively the strength of voluntary contraction of the neophallus as a consequence of reinnervation of the transferred muscle. Furthermore, the data represent a useful tool for clinical assessment and comparison.
Keywords: Transvestism; Muscle Contraction; Nerve Transfer; transvestismus; svalová kontrakce; Electromyography; plastická chirurgie; Muscle, Skeletal; Surgery, Plastic; Humans; elektromyografie; zákroky plastické chirurgie; kosterní svaly; Plastic Surgery Procedures; penis; nervový transfer; Penis; lidé